2009
DOI: 10.1007/s12094-009-0399-6
|View full text |Cite
|
Sign up to set email alerts
|

Late gastrointestinal complications after pelvic radiotherapy: radiation enteritis

Abstract: Radiation enteritis must be initially conservatively managed, but in those cases without response, surgery is indicated. Surgical treatment should not be delayed fearing postoperative complications, which are more susceptible to appear in deteriorated patients. If technically possible, the affected region should be resected, because complications may appear later at this damaged location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
(14 reference statements)
0
12
0
1
Order By: Relevance
“…Kimose et al also found a combination of radiotherapy injuries affecting the colon, rectum, small bowel, or the urinary tract in 62% of their 182 patients 26. According to Ruiz Tovar et al 27, the most common location of late radiation lesions were ileum and rectum, which comprised 60.4% and 24.2% of patients, respectively. Therefore, it is possible that two or more lesions coexist in the same patient.…”
Section: Discussionmentioning
confidence: 97%
“…Kimose et al also found a combination of radiotherapy injuries affecting the colon, rectum, small bowel, or the urinary tract in 62% of their 182 patients 26. According to Ruiz Tovar et al 27, the most common location of late radiation lesions were ileum and rectum, which comprised 60.4% and 24.2% of patients, respectively. Therefore, it is possible that two or more lesions coexist in the same patient.…”
Section: Discussionmentioning
confidence: 97%
“…17 La localización más frecuente de lesión por radiación es el íleon (70%). 18 El daño inducido por radioterapia en tejido de proliferación rápida, tal como la mucosa intestinal, puede ser observado en tan sólo días o semanas. 19 Los cambios en la arquitectura del intestino delgado se pueden dividir en agudos y crónicos.…”
Section: Discussionunclassified
“…The diagnosis of chronic radiation enteritidis requires a great suspicion. The incidence is increasing as more patients undergo radiotherapy for cancer treatment (2). An immunological imbalance probably plays a role in the pathological changes (3).…”
Section: Discussionmentioning
confidence: 99%